Advances in parasitology. Vol. 55, Cumulative subject index, volumes 28-52 - Baker, John R. (John Robin); Muller, Ralph; Rollinson, D.; ScienceDirect eBooks (Oxford : Academic, 2003)
First published in 1963, Advances in Parasitology contains comprehensive reviews in all areas of interest in contemporary parasitology. Now edited by J.R. Baker, R. Muller, and D. Rollinson, and supported by an international editorial board, Advances in Parasitology includes medical studies on parasites of major influence, such as typanosomiasis and scabies, and reviews of more traditional areas, such as zoology, taxonomy, and life history. This index volume chronicles the contents of Volumes 28 through 52 and includes a cumulative subject index and contributor list. * Second in the ISI Parasitology List in 2001 * Enjoys an Impact Factor of 4.097 * Series encompasses over 35 years of parasitology coverage.
Print version record.
Elsevier
Keywords: Parasitology -- Periodicals -- Indexes; Electronic books